2020
DOI: 10.1111/medu.14050
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive appraisals and team performance under stress: A simulation study

Abstract: Objectives The present study explored how challenge and threat responses to stress relate to performance, anxiety, confidence, team identity and team characteristics (time spent in training and postgraduate experience) in a medical simulation‐based team competition. Methods The study was conducted during a national simulation‐based training event for residents, the SIMCUP Italia 2018. The SIMCUP is a simulation competition in which teams of four compete in simulated medical emergency scenarios. Cross‐sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 40 publications
1
8
0
Order By: Relevance
“…Similarly, a literature review examining knowledge of Sim-IPE among practicing nurses indicated a need for Sim-IPE to better understand the roles of other practitioners with whom nurses collaborate. 25 Four studies of a mixed methods design 12,16,26,27 used questionnaires and interviews to study nursing staff perceptions of care transfers of older people. By using Sim-IPE, these studies validated that care transitions were improved, and integrated care skills were developed among hospital staff.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, a literature review examining knowledge of Sim-IPE among practicing nurses indicated a need for Sim-IPE to better understand the roles of other practitioners with whom nurses collaborate. 25 Four studies of a mixed methods design 12,16,26,27 used questionnaires and interviews to study nursing staff perceptions of care transfers of older people. By using Sim-IPE, these studies validated that care transitions were improved, and integrated care skills were developed among hospital staff.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Four studies of a mixed methods design 12,16,26,27 used questionnaires and interviews to study nursing staff perceptions of care transfers of older people. By using Sim-IPE, these studies validated that care transitions were improved, and integrated care skills were developed among hospital staff.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing EOLC is a highly stressful event for nurses, and they experience high levels of stress due to role conflicts, psychological burdens, and time-pressing work as their expertise and clinical competencies increase. Although past findings on stress and performance are somewhat inconsistent, an experimental study reported that stress caused by challenges in task-solving actually improves performance [ 42 ]. This reflects the Yerkes-Dodson law [ 43 ], which explains that an appropriate level of stress is conducive to creative activities and enables problem-solving.…”
Section: Discussionmentioning
confidence: 99%
“…This reflects the Yerkes-Dodson law [ 43 ], which explains that an appropriate level of stress is conducive to creative activities and enables problem-solving. Conversely, increased anxiety due to stress responses can diminish one’s performance [ 42 ]. As repetitive simulation training reduces anxiety [ 44 ], practical education programs may be developed to boost EOLC performance.…”
Section: Discussionmentioning
confidence: 99%